0494 The Associations Between Insomnia Symptoms and Emotional Regulation Among Typically Developing Adolescents during the COVID-19 Pandemic. (25th May 2022) - Scholes, Samantha; Somerville, Gail; Saha, Sujata; Tobia, Jessica; Piccireli, Mikaela; Barnard, Sophia; Patel, Krupali; Gruber, Reut
Abstract: Introduction: A high prevalence of sleep disturbances was observed in adolescents during the coronavirus disease (COVID-19) pandemic. This has been interpreted as being related to disruptions in daily routines and social life caused by pandemic-related societal restrictions. Although the COVID-19 pandemic interrupted the routines of all adolescents, not all adolescents developed insomnia in response to pandemic-related changes. A reduced ability to regulate negative emotions is associated with a higher risk of developing insomnia, yet it is not known if it is associated with higher levels of insomnia in adolescents. Cognitive reappraisal, which consists of changing the way one thinks about potentially emotion-inducing events, is effective in downregulating negative emotion. Expressive suppression, which is changing the way one behaviorally responds to emotion-eliciting events, can decrease a positive emotional experience but does not alter the experience of negative emotion. The objective of this study was to examine the associations between insomnia symptoms in typically developing adolescents during the COVID-19 pandemic and the tendency to use cognitive reappraisal or expressive suppression to regulate emotions. It was hypothesized that high levels of insomnia symptoms among adolescents during the COVID-19 pandemic would be associated with more frequent use of expressive suppression and less frequent use of cognitive reappraisal when regulating emotions. Methods: 49 adolescents aged 11-16 (M= 13.43, SD= 1.67) participated in the study during the first wave of the COVID-19 pandemic in Canada (May 15 to June 30, 2020). The Insomnia Severity Index (ISI) was used to assess the severity of nighttime and daytime components of insomnia. The Emotion Regulation Questionnaire was used to assess respondents' tendencies to regulate their emotions using cognitive reappraisal or expressive suppression. Results: Higher ISI total scores were significantly associated with lower reappraisal scores on the Emotion Regulation Questionnaire. Conclusion: A higher level of insomnia symptoms among typically developing adolescents during the COVID-19 pandemic was associated with less frequent use of emotional regulation strategy that is effective in downregulating negative emotion. Limitations: Given the cross-sectional design of the study, it is not possible to determine causality. Support (If Any): CIHR 418638 to Reut GruberRGPIN-2015-04467 to Reut Gruber